Athletes as community; athletes in community: covid-19, sporting mega-events and athlete health protection - Mann, R. H.; Clift, B. C.; Boykoff, J.; Bekker, S. (British Journal of Sports Medicine, 2020)
The current coronavirus (covid-19) pandemic presents an extraordinary public health challenge. The WHO defines a pandemic as the global spread of a new disease for which there is little or no pre-existing immunity in the human population. Worldwide, we have seen ambitious public health measures implemented by governments, non-governmental organisations and individuals alike. Yet, there is still more to be done to `flatten the curve` and mitigate the impact of this pandemic.